Novel Bis-Thiazole Derivatives: Synthesis and Potential Cytotoxic Activity Through Apoptosis With Molecular Docking Approaches - Dawood, Kamal M.; Raslan, Mohamed A.; Abbas, Ashraf A.; Mohamed, Belal E.; Abdellattif, Magda H.; Nafie, Mohamed S.; Hassan, Mohamed K. (Frontiers in Chemistry, 2021)
A series of bis-thiazoles 5a–g were synthesized from bis-thiosemicarbazone 3 with hydrazonoyl chlorides 4a–g. Reaction of 3 with two equivalents of α-halocarbonyl compounds 6–8, 10, and 12a–d afforded the corresponding bis-thiazolidines 9, 11, and 13a–d, respectively. Condensation of bis-thiazolidin-4-one 9 with different aromatic aldehydes furnished bis-thiazolidin-4-ones 14a–d. Compounds 5a–g, 9, and 13a,c,d were screened in vitro for their cytotoxic activities in a panel of cancer cell lines. Compounds 5a–c, 5f–g, and 9 exhibited remarkable cytotoxic activities, especially compound 5c with potent IC50 value 0.6 nM (against cervical cancer, Hela cell line) and compound 5f with high IC50 value 6 nM (against ovarian cancer, KF-28 cell line). Compound 5f–induced appreciated apoptotic cell death was measured as 82.76% associated with cell cycle arrest at the G1 phase. The apoptotic pathways activated in KF-28 cells treated with 5a, 5b, and 5f were further investigated. The upregulation of some pro-apoptotic genes, bax and puma, and the downregulation of some anti-apoptotic genes including the Bcl-2 gene were observed, indicating activation of the mitochondrial-dependent apoptosis. Together with the molecular docking studies of compounds 5a and 5b, our data revealed potential Pim-1 kinase inhibition through their high binding affinities indicated by inhibition of phosphorylated C-myc as a downstream target for Pim-1 kinase. Our study introduces a set of bis-thiazoles with potent anti-cancer activities, in vitro.